2014
DOI: 10.1159/000365012
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiological Features in Obesity: The Benefits of Body Surface Potential Mapping

Abstract: Background: Various ECG abnormalities are commonly observed in obesity and in metabolic syndrome. Summary: Some of these abnormalities are caused by the pushed-up position of the diaphragm due to obesity and others occur as a result of the complications of the condition. The position of the R wave may change, various arrhythmias may develop or the QT interval may be prolonged, which increases the tendency to malignant arrhythmias. In obesity, the ECG signs of ventricular hypertrophy are less informative due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…ECG is influenced by morphological changes induced by obesity, but conduction intervals (duration of the P wave, QRS complex, and the PQ interval) are not affected by weight loss [ 70 ]. It is well known that the adipose tissue of the human body, especially from the thoracic region, lowers the electric potentials from unipolar leads because it acts as an electric insulation layer [ 71 ]. Beyond the possible interference of adipose tissue with the technical process of capturing the electrical potentials of the heart, changes in electrical intervals are present from the stage of a healthy young adult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECG is influenced by morphological changes induced by obesity, but conduction intervals (duration of the P wave, QRS complex, and the PQ interval) are not affected by weight loss [ 70 ]. It is well known that the adipose tissue of the human body, especially from the thoracic region, lowers the electric potentials from unipolar leads because it acts as an electric insulation layer [ 71 ]. Beyond the possible interference of adipose tissue with the technical process of capturing the electrical potentials of the heart, changes in electrical intervals are present from the stage of a healthy young adult.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect to discuss is the causes of the association of QT prolongation with BFP increase. Several studies have shown that QT interval prolongation is common in obesity, and it shortens with weight loss [ 26 , 71 ]. It seems that the distribution of adipose tissue also influences the values of the QT interval, with upper body obesity exerting a more marked effect [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obezitede ventriküler aritmilere eğilimin arttığını gösteren çalışmalar mevcuttur (14,18). Ventriküler aritmiler, EKG parametrelerinden QT, QTc, QT dispersiyonu ve QTc dispersiyonudur.…”
Section: Discussionunclassified
“…This suggests that the performance of the Polar V800™ in the detection of R-R intervals somewhat declined in adults with hypertension. Typically, a low R-wave amplitude is associated with overweight or obesity [29] due to the electrical insulating role of excess epicardial and subcutaneous adipose tissue on chest wall of individuals with these conditions [9]. Additionally, Bacharova et al [8] found an association between low R-wave amplitude among adults in the early stages of hypertension without structural changes in myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Low R-wave amplitude may be observed in patients with the early stages of hypertension before left ventricular hypertrophy develops, a typical response to chronic high BP [8]. Further, increased chest wall size and epicardial adipose tissue can lead to diminished R-wave amplitude among patients with hypertension since more than 80% of this population are overweight to obese [9]. Moreover, arrhythmias (e.g., premature ventricular contractions) can disrupt R-wave morphology leading to HRV recording errors.…”
Section: Introductionmentioning
confidence: 99%